A Visual Approach to Improving the Experience of Health Information for Vulnerable Individuals - Woollen, Janet (2018)
Many individuals with low health literacy (LHL) and limited English proficiency (LEP) have poor experiences consuming health information: they find it unengaging, unappealing, difficult to understand, and un-motivating. These negative experiences may blunt, or even sabotage, the desired effect of communicating health information: to increase engagement and ability to manage health. It is imperative to find solutions to improve poor experiences of health information, because such experiences heighten vulnerability to poor health outcomes. We aimed to address a gap in the health literacy literature by studying the patient experience of health information and how visualization might be able to help. Our four studies involved patients presented with health information in various settings to improve understanding and management of their care. We used semi-structured interviews and observations to understand patient experiences of receiving personal health information in the hospital. We learned that the return of results is desired and has the potential to promote patient engagement with care. We developed a novel method to analyze LHL, LEP caregiver experience and information needs in the community setting. The novel method increased our understanding and ability to detect differences in experiences within the same ethnic group, based on language preference. Next, we interrogated the literature for a solution to easily communicate complicated health information to disinterested, LHL, LEP individuals. We found that visualizations can help increase interest, comprehension, support faster communication, and even help broach difficult topics. Finally, our findings were used to develop a novel prototype to improve experiences of consuming genetic risk information for those having LHL and LEP. Unlike traditional approaches that focus on communicating risk numbers and probabilities, the novelty of our approach was that we focused on communicating risk as a feeling. We achieved this by leveraging vicarious learning via real patient experience materials (e.g., quotes, videos) and empathy with an emotive relational agent. We evaluated and compared the prototype to standard methods of communicating genetic risk information via a mixed methods approach that included surveys, questionnaires, interviews, observations, image analysis, and facial analysis. Main outcome variables were perceived ease of understanding, comprehension, emotional response, and motivation. We employed t-tests, ANOVAs, directed content analysis, correlation, regression, hierarchical clustering, and Chernoff faces to answer the research questions. All variables were significantly different for the prototype compared to the standard method, except for motivation as rated by 32 LHL, LEP community members. Findings revealed that LHL, LEP individuals have difficulty appropriately processing standard methods of communicating risk information, such as risk numbers supported by visual aids. Further, appealing visuals may inappropriately increase confidence in understanding of information. Visualizations affected emotions, which influenced perceived ease of understanding and motivation to take action on the information. Comprehension scores did not correlate with perceived ease of understanding, emotional response, or motivation. Findings suggest that providing access to comprehensible health information may not be enough to motivate patients to engage with their care; providing a good experience (taking into account the aesthetics and emotional response) of health information may be essential to optimize outcomes.